Sleep quality among Italian university students: the UnSleep multicenter study - Gallè, Francesca; Grassi, Fabiano; Valeriani, Federica; Albertini, Roberto; Angelillo, Silvia; Caggiano, Giuseppina; Bergellini, Annalisa; Bianco, Aida; Bianco, Lavinia; Dallolio, Laura; Della Polla, Giorgia; Di Giuseppe, Gabriele; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Scientific evidence demonstrates that poor sleep quality can lead to various health problems. This study aimed to investigate sleep patterns among Italian university students and identify several factors that may contribute to its quality. Study design. Cross-sectional study. Methods. An electronic questionnaire regarding sociodemographic characteristics, lifestyle, and sleep-related habits, including the Pittsburgh Sleep Quality Index (PSQI) questionnaire, was distributed between January 2022 and July 2023 among students belonging to 12 universities located in Northern, Central, and Southern Italy.